Socio-Economic Abuse of the Victims of Human Trafficking in Arusha Tanzania: A case of women and girl victims - Mkude, Mathias; Sewando, Ponsian; Magesa, Rehema John (Journal of Management Studies and Development, 2024)
Human trafficking has been pervasive around the world with millions of people being trapped in this cycle. The victims of human trafficking encounter many grievances including physical, psychological, sexual, cultural, and even economic abuse. Economic abuse to victims of trafficking is used as a control measure by the perpetrators of human trafficking. In Tanzania, the problem has been persistent with great consequences. It is with this concern that this study embarked on a research journey to examine economic abuse inflicted on the victims of human trafficking. The study applied both probability and nonprobability sampling to select the respondents. A total of 400 respondents were selected for the study. The study revealed that most respondents (72.5%) complained of having big debts built from false accusations from their employers and 74% reported having irregular salary payments respectively. Also, a good number reported working long exhaustive hours with little or no pay (67%).  Only a few respondents (14.1%) reported that they are denied have bank account and if they have, they are not allowed to access it. Also, the study found that 13% of the respondents that their employers had control of their mobile money accounts. They reported that the bosses usually check to see the balance of the accounts.